Digitalization of Coconut Sugar MSME as an Effort to Local Economic Development - Khuzaimah, Rizka Binti; Utomo, Sugeng Hadi (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
The rapid development of technology requires business actors to adapt quickly to survive, including MSME actors. Through a descriptive qualitative approach, the research aims to explain, present, and analyze the role of digitalization in coconut sugar MSME to develop the local economy. This type of research data is in the form of primary data obtained from observation, interviews, and documentation, as well as secondary data obtained from previous literature on related topics. Sampling using purposive sampling, with informants of coconut sugar MSME owners, local communities, and local governments. The results of this study found that the strategy in the use of technology and the use of government empowerment programs have a significant influence on the development of MSME in coconut sugar in Dayu Village, especially in terms of digitalization strategies. However, the reality is that in the field, only one coconut sugar MSME in Dayu Village has digitalized technology, so the role of the government in empowerment still needs to be improved.Adha, L. A. (2020). Digitalisasi Industri Dan Pengaruhnya Terhadap Ketenagakerjaan Dan Hubungan Kerja Di Indonesia. Jurnal Kompilasi Hukum, 5(2), 267-298. Badan Pusat Statistik. (2020). Indikator Kinerja. Diakses pada 16 Desember 2021 melalui https://data.blitarkab.go.id/indikator_kinerja. Badan Pusat Statistik. (2020). Laju Pertumbuhan PDRB Kabupaten Blitar. Diakses pada 17 November 2021 melalui https://blitarkab.bps.go.id/indicator/52/40/1/-seri-2010-laju-pertumbuhan-pdrb-kabupaten-blitar-atas-dasar-harga-konstan-2010-menurut-pengeluaran-.html. Baderi, Firdaus. (2020). Sektor UMKM, Penopang Perekonomian Pasca Covid -19. Diakses pada 21 September 2021 melalui https://www.neraca.co.id/article/134525/sektor-umkm-penopang-perekonomian-pasca-covid-19. Cahyani, F. G., & Sitohang, S. (2016). Pengaruh kualitas produk, kualitas pelayanan dan harga terhadap kepuasan konsumen. Jurnal Ilmu dan Riset Manajemen (JIRM), 5(3). Deloitte. (2015). UKM Pemicu Kemajuan Indonesia: Instrument Pertumbuhan Nusantara. Deloitte Access Economics : Australia. Feriyanto, N. (2018). Determinants of Unemployment in Regency/City in Special Province Yogyakarta. European Research Studies Journal, XXI(3), 367–380. https://doi.org/10.35808/ersj/1388 Feriyanto, N. (2019). The Effect of The Quality of Human Development Factors on The Rate of Economic Growth In Yogyakarta Special Province. International Journal for Quality Research, 13(1), 157-176. Ghobakhloo, M., Sabouri, M.S., Hong, T.S., Zulkifli, N. (2011). Information Technology Adoption in Small and Medium-sized Enterprises; An appraisal of two literature. Interdisciplinary Journal of Research in Business, 1 (7), pp. 53-80 Hamid, E. S., & Susilo, Y. (2011). Strategi pengembangan usaha mikro kecil dan menengah di Provinsi Daerah Istimewa Yogyakarta. Setiawan, H. (2012). Pengaruh Orientasi Pasar, Orientasi Teknologi dan Inovasi Produk terhadap Keunggulan Bersaing Usaha Songket Skala Kecil di Kota Palembang, Jurnal Orasi Bisnis Edisi ke-VIII, hlm. 13 Idah, Y. M., & Pinilih, M. (2020). Strategi Pengembangan Digitalisasi UMKM. Prosiding, 9(1). Idrus, Muhammad. (2009). Metode Penelitian Ilmu Sosial, Pendekatan Kualitatif dan Kuantitati. Jakarta: Erlangga. Indrajit, R. E. (2000). Manajemen sistem informasi dan teknologi informasi. Jakarta: PT Elex Media Komputindo. Kemenkop. (2019). Data Perkembangan Kemenkopukm. Diakses pada 21 September 2021 melalui https://kemenkopukm.go.id/uploads/laporan/1617162002_SANDINGAN_DATA_UMKM_2018-2019. Maulana, Yosa. (2017). Yuswohady: UKM Harus Manfaatkan Perkembangan Digital. Diakses pada 22 Desember 2021 melalui https://swa.co.id/swa/csr-corner/yuswohady-ukm-harus-manfaatkan-perkembangan-digital. Nasution, E. Y., & Indria, T. (2021). Digitalisasi Umkm Di Masa Pandemi. In Prosiding Seminar Nasional Kewirausahaan (Vol. 2, No. 1). Pinem, D., Pusporini, P., & Masnuna, M. (2022). Digitalisasi Manajemen Pada Usaha Kecil Dan Menengah (UMKM) Di Depok Jawa Barat. IKRA-ITH ABDIMAS, 5(1), 172-183. Polnaya, G. A., & Darwanto, D. (2015). Pengembangan ekonomi lokal untuk meningkatkan daya saing pada ukm ekonomi kreatif batik bakaran di pati, jawa tengah. Jurnal Bisnis dan Ekonomi, 22(1). Purwana, D., Rahmi, & Aditya, S. (2017). Pemanfaatan Digital Marketing Bagi Usaha Mikro, Kecil, dan Menengah (UMKM) Di Kelurahan Malaka Sari, Duren Sawit. Jurnal Pemberdayaan Masyarakat Madani (JPPM) 1(1): 1 – 17 Sinaga, A. A. P. (2017). Faktor-faktor yang Mempengaruhi Pengembangan Ekonomi Lokal (Pel) di Kota Medan (Studi Kasus USAha Kecil dan Menengah sebagai Sektor Basis). Jurnal Manajemen dan Bisnis, 17(1), 74-84. Srirejeki, K. (2016). Analisis Manfaat Media Sosial Dalam Pemberdayaan Usaha Mikro Kecil Dan Menengah (Umkm) Analysis Of The Use Of Social Media To Empower Small Micro Medium Enterprise (Smes). Uitz, I., 2012. Social Media – Is It Worth the Trouble? Journal of Internet Social Networking & Virtual Communities. 2012 (2012), 313585 Undang-Undang No. 22 Tahun 1999 tentang Pemerintahan Daerah. Undang-Undang No. 25 Tahun 1999 tentang Pertimbangan Keuangan. Undang-Undang Republik Indonesia No. 20 Tahun 2008 tentang UMKM. Winartha, I Made. 2006. Pedoman Penulisan Usulan Penelitian, Skripsi dan Tesis. Yogyakarta: Andi.